APPRENTICESHIP VOCATIONAL TEACHERS MANAGEMENT - Usep - (Fakultas Pendidikan Islam dan Keguruan Universitas Garut, 2018)
The focus of the study is to analyze the vocational school productive teacher apprenticeship of motorcycle engineering skill package based on partnership at the Learning Center of PT. Daya Adicipta Motora (DAM) and Astra Honda Authorized Service Station (AHASS) that consists of policies, activities, funding, and monitoring and evaluation support. The purpose of this study is to describe support of policies, activities, funding, monitoring and evaluation and it can formulate hypothetical model of teacher apprenticeship. The position and importance of teacher apprenticeship are to improve teacher professionalism, the relevance, and the quality of vocational education. The research method used is a case study. Data are collected through interview, observation and documentation. Analysis of data is through data reduction, data presentation, conclusion withdrawal, and verification. The result shows: policy support of teacher apprenticeship is explicitly not available because it still refers to policy of students industrial practices; activities of teacher apprenticeship must be planned carefully; the financing of teacher apprenticeship is obtained from APBN/APBD, society, business world, and industry world; the operational finance is from vocational school; the finance of teacher apprenticeship implementation is borne by business and industry world, and monitoring and evaluation of teacher apprenticeship are conducted by PT. DAM /AHASS through pretest and posttest. Recommendation: Teacher apprenticeship needs determination of policy support from stakeholders, in order to improve the teacher professionalism